A total neoadjuvant chemotherapy approach is associated with improved recurrence‐free survival in patients with colorectal peritoneal metastases undergoing cytoreductive surgery and HIPEC. Issue 3 (9th November 2022) - Hanna, David N.; Macfie, Rebekah; Ghani, Muhammad O.; Hermina, Andrew; Mina, Alexander; Cha, Da Eun; Bailey, Christina E.; Cohen, Noah; Labow, Daniel; Golas, Benjamin; Sarpel, Umut; Magge, Deepa; et al.
Abstract: Background: The primary aim of this study is to evaluate the oncologic outcomes of two popular systemic chemotherapy approaches in patients with colorectal peritoneal metastases (CPM) undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS‐HIPEC). Methods: We performed a dual‐center retrospective review of consecutive patients who underwent CRS‐HIPEC for CPM due to high or intermediate‐grade colorectal cancer. Patients in the total neoadjuvant therapy (TNT) group received 6 months of preoperative chemotherapy. Patients in the "sandwich" (SAND) chemotherapy group received 3 months of preoperative chemotherapy with a maximum of 3 months of postoperative chemotherapy. Results: A total of 34 (43%) patients were included in the TNT group and 45 (57%) patients in the SAND group. The median overall survival (OS) in the TNT and SAND groups were 77 and 61 months, respectively ( p = 0.8). Patients in the TNT group had significantly longer recurrence‐free survival (RFS) than the SAND group (29 vs. 12 months, p = 0.02). In a multivariable analysis, the TNT approach was independently associated with improved RFS. Conclusion: In this retrospective study, a TNT approach was associated with improved RFS, but not OS when compared with a SAND approach. Further prospective studies are needed to examine these systemic chemotherapeutic approaches in patients with CPM undergoing CRS‐HIPEC.